2017
DOI: 10.3390/ijerph14070798
|View full text |Cite
|
Sign up to set email alerts
|

Online Vape Shop Customers Who Use E-Cigarettes Report Abstinence from Smoking and Improved Quality of Life, But a Substantial Minority Still Have Vaping-Related Health Concerns

Abstract: (1) Background: Characteristics and usage patterns of vapers (e-cigarette users) have mainly been studied in web-based convenience samples or in visitors of brick-and-mortar vape shops. We extended this by targeting customers of one particular online vape shop in the Netherlands; (2) Methods: Customers were questioned on their smoking history, current smoking and vaping status, reasons for vaping, perceived harmfulness, and potential health changes due to vaping; (3) Results: Almost everyone (99%, 95% CI 0.96,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 20 publications
9
27
1
Order By: Relevance
“…In line with this, participants bought 3rd/4th generation e-cigarettes but noteworthy, e-liquid with a nicotine concentration of on average no more than 7 mg/mL. This nicotine concentration is in the same range as observed in two other studies in Flemish/Dutch vapers, where online vape shop customers (eight in 10 complete switchers) used on average 9.7 mg/mL of nicotine and 4–8 mg/mL of nicotine was the most frequent choice in both dual users and switchers of another more recent convenience sample [ 38 , 39 ]. However, when taking into account not only the nicotine concentration but also the volume of e-liquid consumed per week, it must be noted that the overall volume of about 13 mL/week in the current study is substantially lower than the 19.5 mL/week in the Van Gucht and colleagues sample and definitely lower than the 38.1 mL/week in the Adriaens and colleagues sample (23.7 mL/week in dual users, 41.4 mL/week in switchers) [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 80%
“…In line with this, participants bought 3rd/4th generation e-cigarettes but noteworthy, e-liquid with a nicotine concentration of on average no more than 7 mg/mL. This nicotine concentration is in the same range as observed in two other studies in Flemish/Dutch vapers, where online vape shop customers (eight in 10 complete switchers) used on average 9.7 mg/mL of nicotine and 4–8 mg/mL of nicotine was the most frequent choice in both dual users and switchers of another more recent convenience sample [ 38 , 39 ]. However, when taking into account not only the nicotine concentration but also the volume of e-liquid consumed per week, it must be noted that the overall volume of about 13 mL/week in the current study is substantially lower than the 19.5 mL/week in the Van Gucht and colleagues sample and definitely lower than the 38.1 mL/week in the Adriaens and colleagues sample (23.7 mL/week in dual users, 41.4 mL/week in switchers) [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 80%
“…Surveys of e-cigarette users suggest that e-cigarettes are used as smoking-cessation aids, while a large proportion of e-cigarette users manage to quit smoking or substantially reduce smoking consumption. 144 147 However, these studies use convenience samples, suffer from selection bias and cannot represent the general population. A study of vapeshop customers objectively assessed the smoking status of participants by measuring exhaled carbon monoxide and identified that 66% of participants had quit smoking.…”
Section: Efficacy In Smoking Cessation and Reductionmentioning
confidence: 99%
“…As reported in the results section, across all 97 e-liquids tested, benzene concentration levels ranged from 2.7 µg/L (in samples 3-B and 6-D, both produced in Italy) to 30,200.0 µg/L (sample 3-A produced in China). This means that, if we consider the daily average consumption of e-liquids by a regular vaper approximately equal to 3 ml per day [48], the total amount of benzene potentially inhaled by the vaper within one day would have ranged from 0.0081 µg to 90.6 µg. For the most contaminated Chinese brand (brand A) the total amount of daily inhaled benzene with 3 ml e-liquid consumption would have varied in the range 21.6-90.6 µg.…”
Section: Discussion On Btex Resultsmentioning
confidence: 99%
“…The remaining 38 e-liquids were declared nicotine-free. Most of the investigated e-liquids were flavored and may be included in the following typical flavor categories: tobacco (48), mint (17), sweets/candy (11), spicy (7), fruits (3), coffee (3), and alcohol (3). Before analysis, all e-liquids were properly stored at room temperature and kept away from direct sunlight, as recommended on the product label.…”
Section: E-liquids Selectionmentioning
confidence: 99%